Evaluation of carbon fiber reinforced cementitious matrix as a recyclable strengthening material. (20th April 2019) - Li, Wan-qian; Zhu, Ji-Hua; Chen, Pi-yu; Xing, Feng; Li, Dawang; Su, Meini
Abstract: The use of fiber-reinforced polymer (FRP)-epoxy resin is a common retrofitting technique usually employed by engineers. In the research presented in this paper, a new cement-based material was developed introducing chopped carbon fiber. The carbon-fiber-reinforced cementitious matrix (C-FRCM) containing a cement-based matrix and embedded carbon-fiber mesh is an alternative solution to FRP-epoxy resin, addressing cost, durability, and reversibility issues. The flexural performance of carbon-fiber-reinforced cementitious matrix plates with chopped carbon fibers was explored in this study. A series of three-point bending tests were conducted to investigate the effects of chopped carbon fiber content. The measured mechanical properties of the proposed C-FRCM mix were compared with those made of commercial formulations. The flexural strengths and failure modes of the carbon-fiber-reinforced cementitious matrix plates were obtained and recorded during tests, and then the interlaminar shear strengths were calculated. Upon the completion of three-point bending tests, scanning electron microscopy was used to observe the microscopic appearance of tested specimens. The optimum content of chopped carbon fibers in the cement-based materials was determined based on the structural behavior and microstructural analysis. The results also show that the carbon fiber mesh is effective in strengthening the carbon-fiber-reinforced cementitious matrix.